Digital Capabilities, Environment, And Business Strategy For Msmes Performance In Sidoarjo District - Deby Andriani Jumaroh; Diah Hari Suryaningrum (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to test and prove the influence of environmental factors, business strategy, digital literacy, and digital skills on the performance of MSMEs. Quantitative research is a type of research that uses primary data. Questionnaires are used to collect data. The population of this research is MSMEs in Sidoarjo Regency, according to data from the Department of Cooperatives and Micro Enterprises (Ditakopum). The sampling technique used purposive sampling, and 162 business actors or MSME owners were respondents whose data could be processed. The variant-based Structural Equation Modeling (SEM) or Partial Least Square (PLS) model was used to analyze the data via SmartPLS version 4.0 software. The results of this research explain that business strategy, digital literacy, and digital skills influence the performance of MSMEs. However, environmental factors do not influence the performance of MSMEs. This indicates that in the current digital era, digital skills and the ability to create business strategies are very important for MSMEs. The implication is that the government can further intensify digital training for MSME owners as a business strategy to achieve MSME sustainability.